Martyn Lloyd-Jones (1899-1981) and twentieth century evangelicalism - Brencher, John (Carlisle, UK Paternoster, 2002)
Includes biblographical references and indexes.
Originally published as a Doctroral thesis, 1997, History Department, University of Sheffield
Keywords: Lloyd-Jones, David Martyn, -- Dr., -- 1899-1981; Church history -- 20th century -- biography; Evangelicalism -- biography